2019
DOI: 10.3390/pharmaceutics11100513
|View full text |Cite
|
Sign up to set email alerts
|

Swelling of Zein Matrix Tablets Benchmarked against HPMC and Ethylcellulose: Challenging the Matrix Performance by the Addition of Co-Excipients

Abstract: Zein is an insoluble, yet swellable, biopolymer that has been extensively studied for its applications in drug delivery. Here, we screened the effect of co-excipients on the swelling and drug release of zein tablets. All throughout the study the behavior of zein was benchmarked against that of hydroxypropyl methylcellulose (HPMC) and ethylcellulose (EC). Tablets containing either zein, HPMC, or EC alone or in combination with co-excipients, namely lactose, dicalcium phosphate (DCP), microcrystalline cellulose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In fact, the Zein-based nanomaterials have been found to possess excellent swelling properties in an aqueous solution, which is an added advantage along with their high biocompatibility [49]. For example, Berardi et al reported the swelling behavior of Zein, finding that it could be enhanced with the addition of co-excipients [50]. Taking advantage of this, we hypothesized that once the NIC molecules are encapsulated inside the Zein and injected after the BSA coating, they would work selectively, getting taken up by the damaged endothelial glycocalyx present in most elderly COVID-19 patients.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…In fact, the Zein-based nanomaterials have been found to possess excellent swelling properties in an aqueous solution, which is an added advantage along with their high biocompatibility [49]. For example, Berardi et al reported the swelling behavior of Zein, finding that it could be enhanced with the addition of co-excipients [50]. Taking advantage of this, we hypothesized that once the NIC molecules are encapsulated inside the Zein and injected after the BSA coating, they would work selectively, getting taken up by the damaged endothelial glycocalyx present in most elderly COVID-19 patients.…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…The swelling index was highest for formulation F 6 (50.69% polymer) and least for F 5 (24.21% polymer). This is attributed to the presence of highly hydrophilic hydroxypropyl groups in HPMC [ 26 , 27 ]. The hydration of these functional groups results in rapid ingress of medium in polymer network, ultimately causing swelling and ordering of polymer chains [ 26 ].…”
Section: Resultsmentioning
confidence: 99%